Computational science and its applications -- ICCSA 2020 : 20th International Conference, Cagliari, Italy, July 1-4, 2020, Proceedings.: 20th International Conference, Cagliari, Italy, July 1-4, 2020, Proceedings. Part V (2020) - Unknown
No abstract available